Probiotic low-fat fermented goat milk with passion fruit by-product: In vitro effect on obese individuals’ microbiota and on metabolites production - Neves Casarotti, Sabrina [UNESP]; Fernanda Borgonovi, Tais [UNESP]; de Mello Tieghi, Thatiana [UNESP]; Sivieri, Katia [UNESP]; Lúcia Barretto Penna, Ana [UNESP] (Elsevier, 2020)
This study aimed to evaluate the impact of a two-week treatment period with probiotic low-fat fermented goat milk by Lactobacillus casei Lc-1, supplemented with passion fruit by-product (1%), on the modulation of gut microbiota from obese individuals using the Simulator of Human Intestinal Microbial Ecosystem (SHIME) system. The effects were carried out through the study of gut microbiota composition, using 16S rRNA next generation sequencing, quantification of short-chain fatty acids (SCFA) and ammonium ions. The microbiota composition changed across three vessels representing the colon regions, because of fermented milk treatment. Fermented goat milk administration caused a reduction of bacteria belonging to genera Prevotella, Megamonas and Succinivibrio, which can produce SCFA, and an increase of Lactobacillus and Bifidobacterium genera in all simulated colon regions. There was no effect on SCFA and on ammonium ions concentration during treatment period. Fermented milk shifted the obese donors’ microbiota without changing metabolites production. It happens, possibly, due to a balance in abundances among bacterial genera that can produce or not SCFA, and among bacterial genera with high or low proteolytic activity. Our outcomes help to clarify the effects of the ingestion of a probiotic low-fat fermented goat milk product on colon microbiota composition.
Keywords: 16S rRNA sequencing; Fruit by-product; Gut microbiota; Lactobacillus casei Lc-1; Obesity; Probiotic fermented food; SHIME® system